Experiência em estágios e intercâmbios durante a graduação em Medicina - Ferreira, Brenda Emanuelly de Campos (Universidade Federal de São Carlos, 2024)
This undergraduate thesis in medicine at the Federal University of São Carlos (UFSCar) is an experiential report of placements at the Santa Casa de Misericórdia in Anápolis, Goiás, Brazil, and at the Clermont-Ferrand University Hospital Estaing in France. The study highlights the benefits of practical learning for medical students, such as exposure to different hospital and cultural contexts, which contributes to a more humanized medical education. The challenges and achievements of these placements and academic exchanges are discussed, highlighting the importance of practical experience in developing professional and personal skills. The work aims to inspire other students to seek similar experiences and to make the academic journey more accessible by sharing information about the frequency of public calls and the importance of internship and exchange opportunities.
Experience in interships and exchanges during medical school
Keywords: Estágio médico; Intercâmbio acadêmico; Formação em saúde; Aprendizagem prática; Ensino médico; CIENCIAS DA SAUDE::MEDICINA